2007
DOI: 10.1161/circulationaha.107.691154
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of the Right Ventricular Filling Pressure Gradient

Abstract: Background-The physiological basis of right ventricular (RV) diastolic function remains incompletely studied in humans.The driving force responsible for RV filling, the pressure gradient along the RV inlet from the right atrium to the RV apex, has never been measured in the clinical setting. Methods and Results-We validated a method for measuring the RV filling pressure difference (RVFPD) from color Doppler M-mode recordings in 12 pigs undergoing interventions on RV preload, afterload, and lusitropic states (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…32 A noninvasive study has also suggested the presence of a diastolic filling gradient in humans. 33 A major caveat to the above is that we do not have data on diastolic stiffness or RV volume for our patients. Further study is needed to clarify the relative impact on RV filling pressures of changes in these factors versus active relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…32 A noninvasive study has also suggested the presence of a diastolic filling gradient in humans. 33 A major caveat to the above is that we do not have data on diastolic stiffness or RV volume for our patients. Further study is needed to clarify the relative impact on RV filling pressures of changes in these factors versus active relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…В этом плане привлекательно выглядит оценка диастолической функции ПЖ, которая, с одной стороны, является марке-ром ранней или скрытой дисфункции ПЖ [7,8], а с дру-гой -также может иметь независимое прогностическое значение [9]. Работы последних лет показали, что оцен-ка диастолической функции ЛЖ может проводиться с помощью различных показателей как на основе анали-за транстрикуспидальных потоков и распространения их в полости ПЖ, так и движения стенок ПЖ [10,11]. Показано, что они могут иметь различное клиническое значение в выявлении нарушений наполнения ПЖ [12], однако их относительное прогностическое значение пока мало изучено.…”
Section: Discussionunclassified
“…При определении этого показа-теля в режиме непрерывно-волновой допплерометрии отмечалось увеличение риска смерти в 1,3 раза при его увеличении на 0,1 [23]. С появлением спектральной тка-невой допплерометрии определение индекса Теи ПЖ значительно упростилось, а его определение было вклю-чено в необходимый минимум рекомендованных пока-зателей функции ПЖ [10]. Информативность индекса Теи подтверждается и в ходе контроля за результатами тромбэндартерэктомии [24] и митральной комиссу-ротомии [25].…”
Section: результаты исследованияunclassified
“…While these experiments demonstrate the role of nonconvective, or inertial, forces for transmitral flow, it is important to consider that the same principles apply for other applications that measure pressure gradients within the heart, such as intraventricular pressure gradients [16, 17], right ventricular filling pressures [18], intracardiac shunts, and pulmonary hypertension [19]. For example, while Doppler velocities are routinely used to derive pulmonary artery pressures [20], it is well known that these pressures typically correlate poorly with actual catheter-derived measurements [21].…”
Section: Clinical Datamentioning
confidence: 99%